Pengaruh Problem-Based Learning dengan Permainan “Jelajah Waktu” terhadap Kemampuan Pemecahan Masalah Matematis di SD - Wahyuni, Siti; Isrok’atun, Isrok’atun; Maulana, Maulana (SJME (Supremum Journal of Mathematics Education), 2024)
This research aims to find out how the problem-based learning (PBL) model with the "Time Exploration" game affects students' mathematical problem solving abilities, as well as to find out which learning model is better. This type of research is quasi-experimental with a pretest-pottest control group design research design. The population used was class III elementary school students in South Sumedang District with a research sample of class III at SDN Sukaraja II. The problem solving ability test with descriptive questions was the instrument in this research. Then the data analysis technique was carried out using the average difference test (paired sample t-test and independent sample t-test) and the gain test which was previously tested for normality and homogeneity. The research results show that there is a positive influence through the application of the PBL model with the "Time Exploration" game on students' problem solving abilities and shows an increase of 0.46 in the experimental class which is classified as a moderate increase. Then, it was also concluded that PBL learning with the "Time Exploration" game was better than conventional learning.